Reproductive correlates of eggshell thickness in European woodpeckers - Hogstad, Olav (Ornis Norvegica, 2008)
Woodpeckers excavate their own nesting holes, have small eggs relative to their body size and many species have small clutches. Based on data from the eight European woodpecker species it was found that the mean thickness of eggshells increases with egg volume, whereas large woodpeckers lay smaller eggs with thinner eggshell relative to their body mass. It is speculated that woodpeckers minimize their reproductive costs by laying energy-poor eggs that are relatively cheap to produce, and with their low adult mortality rates, increase their lifetime reproductive success.